Quebra de dormência em túberas e indução de tuberização em estacas caulinares de inhame (Dioscorea sp.) - Santos, Crislaine Alves (2020)
Yam, belonging to the Dioscoreaceae family, is a crop whose production is related to family farming and its consumption in Brazil is associated with the Northeastern culture. It is a tuberous vegetable of vegetative propagation through seed tubers, mainly obtained through the capping process. However, this method adopted by producers has limitations such as high acquisition cost and sprout unevenness, which contributes to low crop yield. Thus, this research was conducted with the objective of evaluating the dormancy break of commercial yam and seed tubers submitted to different ethylene concentrations and to evaluate the production of minitubers from stem cuttings. For breaking dormancy of commercial yam, a randomized block design in a 4x2x3 factorial scheme was used, with four concentrations of Ethrel® (0, 10, 20 and 40 mL.L-1), two rest periods (with and without rest) and three positions in the tuber (head, middle and tail), with five repetitions. For the seed tuber, a randomized block design in a 4x2 factorial scheme was used, with four concentrations of Ethrel® (0, 10, 20 and 40 mL.L-1) and two rest periods (with and without physiological rest). For the cuttings, the experimental design was completely randomized in a 3x3 factorial scheme, being three regions of the plant to obtain the cut (apical, median and basal) and three commercial substrates (Forest Tropstrato, Vegetables Tropstrato and the mixture of the two substrates in 1:1 ratio). Additionally, the development of the minituber was followed by histological sections. The different positions, concentration of Ethrel® and rest period influenced the average time of commercial yam sprouting, while for seed tubers the factors studied did not influence the sprouting. The median cuttings presented larger diameter and fresh mass of minitubers, and 75% of them produced two minitubers using the Forest Tropstrato substrate. It was observed, by anatomical study, that seven days after cut’s planting the process of cell division began and starch accumulation in the nodal region, and with 21 days it was possible to visualize the rise of the minituber.